Intertextualidade e letramento : a leitura e a interpretação dos elementos intertextuais do gênero multimodal meme como ferramenta para a construção de um leitor competente - Santos, Roberto Lopes dos (2020)
The present study aims to promote the development of the reading competence of students in the 8th grade of Elementary School of the Colégio Estadual Professor Antônio Fontes Freitas, located in the municipality of Nossa Senhora do Socorro-SE, based on the intertextuality present in the multimodal meme genre, contributing for the practice of literacies, linguistic literacy, digital literacy and multi-literacy. Observe, through a diagnostic test, that students in the class are presenting a low level of reading competence and interpretive perception to infer about the intertextuality present in the texts read. Given the data, students use the Internet for various purposes, such as, for example, socializing and searching for information, defining the genre of digital meme, which is very popular among young people, as the textual genre and being worked on. For the treatment of the problem, a Didactic Sequence was developed, based on the suggestion of Dolz, Noverraz and Schneuwly (2004). This SD model is divided into four phases: Presentation of the situation; First production; Development of modules and workshops and final production. The application of this sequence provides students with the possibility to learn and discuss how situations involving a digital genre fabric, through the aspects of multimodality and intertextuality existing in the genre. The research developed here had a theoretical and methodological reference based on the postulates on Reading, Literacy, Digital Literacy, Multiliteracies and Multimodality, in Soares (2003), Kleiman (2007), Marcuschi (2005), Boton (1998), Tapscott (1999), Rojo (2009), Dionísio (2007; 2011), Coscarelli (2007), Kleiman (2007) and Freitas (2010); on Reader and Reading, in Chartier (1998), Freire (2005) and Kleiman (2000); on New Information and Communication Technologies, in Prensky (2001), Menezes and Santos (2017), Rodrigues (2012), Sampaio and Leite (1999), Santos, Beato and Aragão (2012) and Gomes (2010); on the Digital Genre Meme, in Dawkins (1979), Recuero (2010) and Castro and Cardoso (2015); and on Dialogism and Intertextuality, in Bakthin (2000), Kristeva (1974), Koch (1995; 2008) and Bazerman (2006); on pedagogical games, in Huizinga (2000) and Lopes (2001). The application of the developed pedagogical proposal, offered to the participants involved, a gradual development of reading and discourse competence, as well as substantial access to the possibilities of multi-tools, present in the construction of the digital gender meme and without recognition of the elements of intertextuality. In this way, as a final result, a significant advance of the students is pointed out, while the authorized and advanced readers for reading inside and outside the school.